PEMANFAATAN SIMPLISIA DAUN UNGU SEBAGAI UPAYA PENINGKATAN NILAI TAMBAH EKONOMI MASYARAKAT KELURAHAN LAMBARA, KECAMATAN TAWAELI - Niluh Puspita Dewi; Joni Tandi; Syafika Alaydrus; Fadillah Insani (Jurnal Abdi Insani, 2026)
Lambara Urban Village, Tawaeli District, continues to experience multiple family health challenges, including among residents living in temporary shelters. Preliminary observations identified complaints related to degenerative diseases, particularly diabetes mellitus, indicating the need for community-participatory education on prevention and self-management. Purple leaf (Graptophyllum pictum) is a herbal resource with potential to support diabetes control; however, its utilization in the community remains suboptimal due to limited access to adequate information. This community service program aimed to improve health literacy and practical skills among residents of RT 09, Lambara Urban Village, by introducing simplisia processing to strengthen the use of local resources. The program comprised a preparatory phase (literature review and development of educational materials), followed by outreach delivered through lectures, banner-based media, and leaflet distribution, to address constituents processing and utilization of purple leaf. Outcomes were assessed using pre-test and post-test, complemented by basic health screening and pharmacist-led consultations. The activity was implemented on Tuesday, 13 January 2026, by a team of lecturers and students from STIFA Pelita Mas Palu, involving 27 participants. The results indicated improved participant understanding and encouraged the adoption of healthier lifestyle practices.